2007
DOI: 10.1111/j.1471-4159.2007.04528.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of hippocampal neuronal nitric oxide synthase contributes to the stress‐related deficit in learning and memory

Abstract: Nitric oxide (NO) has been involved in many pathophysiolog-ical brain processes. However, the exact role of NO in the cognitive deficit associated to chronic stress exposure has not been elucidated. In this study, we investigated the participation of hippocampal NO production and their regulation by protein kinase C (PKC) in the memory impairment induced in mice subjected to chronic mild stress model (CMS). CMS mice showed a poor learning performance in both open field and passive avoidance inhibitory task res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 65 publications
(72 reference statements)
3
30
0
1
Order By: Relevance
“…We found that chronic mild stress (CMS) increased hippocampal NO production by nNOS in male mice (6)(7)(8)(9). In contrast, CMS diminished hippocampal NO production by nNOS in female mice (14). Here we show that hippocampal NO plays a role in the sex difference of depression-like behaviors in rodents.…”
mentioning
confidence: 57%
“…We found that chronic mild stress (CMS) increased hippocampal NO production by nNOS in male mice (6)(7)(8)(9). In contrast, CMS diminished hippocampal NO production by nNOS in female mice (14). Here we show that hippocampal NO plays a role in the sex difference of depression-like behaviors in rodents.…”
mentioning
confidence: 57%
“…In this study, to examine whether chronic stress modifies circadian rhythms of hepatic clock genes, we chose a CMS model that has been widely used for producing a state of chronic stress (34,38,39,53). This CMS procedure consists of stressors, including water deprivation, food deprivation, and 12-h overnight illumination, all of which can affect circadian expression rhythms of clock genes in peripheral tissues (11,32).…”
Section: Discussionmentioning
confidence: 99%
“…First, to examine the influence of chronic stress on circadian clock gene expressions in the liver, BALB/c mice were divided into two groups: one was housed under ordinary conditions (Control-BALB) and the other was subjected to CMS (CMS-BALB) (34,38,39,53). Serum parameters and hepatic gene expressions were analyzed 1 day after the last day of CMS (Fig.…”
Section: Cms Alters Circadian Mrna Expression Profiles Of Core Clock mentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that nitric oxide (NO) signaling might also be disrupted by PCBs and other endocrine disrupting chemicals (EDCs, Sharma and Kodavanti, 2002;Martini et al, 2010;Currá s-Collazo, 2011). NO which is produced by nitric oxide synthase (NOS), is a gaseous neurotransmitter that serves an important role in neuroendocrine function (Garthwaite and Boulton, 1995), in synaptic processes associated with learning and memory such as a retrograde messenger underlying long term potentiation (LTP), (Bohme et al, 1991;O'Dell et al, 1991;Schuman and Madison, 1991), and in neurodegeneration (Liberatore et al, 1999;Palumbo et al, 2007). Therefore, results from studies on the effect of EDCs on NO signaling can inform significantly about the broad range of adverse effects produced by these neuroactive chemicals.…”
Section: Introductionmentioning
confidence: 99%